Effect of soft segment and clay volume fraction on rate dependent damping of polyurethane and polyurethane-clay nanocomposites. (December 2014) - Sain, Trisha; Yeom, Bongjun; Waas, Anthony M; Arruda, Ellen M
Amorphous polymers have been extensively used for energy dissipative applications due to their relatively low density and controllable rate dependent damping. In general, molecular mobility depends on the rate of applied loading and the ambient temperature, and results in a wide variety of mechanical properties. The variation in the macromolecular chain dynamics can be obtained by altering the chemical architecture and morphology of the constituent monomers. The present study is focused on finding a correlation between the chemical structure of the constituent monomer and the rate dependent viscous damping of the macromolecules. Polyurethane (PU) made up of isophorone diisocyanate (IPDI) and polycaprolactone diol (PCL) is considered to estimate the effect of soft segments (diol content) on damping property of PU. A linear viscoelastic mathematical model (based on standard-linear solid (SLS) model) is used to extract the rate dependent relaxation time constants for the materials. It is found that increasing the soft segment content in the PU does not improve damping limitlessly. Beyond a critical percentage of soft segment content, characteristic relaxation times have a significant drop. Further, the analysis is extended for PU-clay nanocomposites and a correlation between the clay volume fraction and relaxation constants is established. The study will help to choose and design PU and volume percentage of clay nanoparticle for manufacturing PU-clay nanocomposites with desired damping property.